Crystal structure and supramolecular features of O-ethyl pivaloylcarbamothioate: insights from Hirshfeld surface and energy framework analyses - Uslu, Salih; Solmaz, Ummuhan; Arslan, Hakan (European Journal of Chemistry, 2025)
The crystal structure of O-ethyl pivaloylcarbamothioate has been determined by single-crystal X-ray diffraction. The compound crystallizes in the orthorhombic crystal system, the space group Pbca, with unit-cell dimensions a = 10.144(9) Å, b = 10.230(6) Å, c = 19.934(19) Å. The unit-cell volume is 2069(3) Å3 with Z = 8 at 298.15(2) K. A crystal specimen of size 0.241 × 0.217 × 0.124 mm3 was used for data collection using CuKα radiation (λ = 1.54178 Å). The measured reflections (25,062 in total) covered the index ranges −12 ≤ h ≤ 12, −12 ≤ k ≤ 13, and −25 ≤ l ≤ 25, of which 2246 were unique (Rint = 0.1349, Rsigma = 0.0658). The refinement converged with the final values R1 = 0.0942 [I > 2σ(I)] and wR2 = 0.2485 (all data), giving a calculated density of 1.216 g/cm3 and the absorption coefficient μ = 2.506 mm-1. The crystal structure of the title compound is stabilized by a hierarchical supramolecular architecture involving both classical (N-H···O) and non-classical (C-H···O, C-H···N, C-H···S) hydrogen bonds, giving rise to triangular, zigzag, and cyclic motifs as well as and synthons. Hirshfeld surface and fingerprint analyses confirm that H···H contacts dominate the packing, whereas directional H···O and H···S interactions play a crucial role in lattice cohesion. Interaction energy calculations further reveal that electrostatic and dispersion forces are the main contributors to the stabilization of the three-dimensional framework.